Conservation agriculture practices in Indian mustard (Brassica juncea)-basedcropping systems for enhanced productivity and profitability - JAT, R S; SINGH, H V; CHOUDHARY, R L; MEENA, M K; RAI, P K (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during 2019–20 and 2020–21 at the research farm of ICAR-Directorate of Rapeseed-Mustard Research, Bharatpur, Rajasthan to scale out the conservation agriculture (CA) practices in Indian mustard [Brassica juncea (L.) Czern.]-based cropping systems for enhancing production and farm profitability. Experiment was conducted in the split-plot design (SPD) after randomization, and replicated three times in the permanent plots. The treatment comprised of 3-tillage and crop residue re-cycling [permanent beds with residue (PB+R); zero tillage with residue (ZT+R); and conventional tillage without residue (CT-R)] in main-plots; and 6-oilseed brassica-based cropping systems [Fallow-mustard (F-M); Cluster bean [Cyamopsis tetragonoloba (L.) Taub.]-mustard (CB-M); Greengram [Vigna radiata (L.) R. Wilczek-mustard (GG-M); Maize (Zea mays L.)-mustard (Mz-M); Pearl millet [Pennisetum glaucum (L.) R. Br.]-mustard (PM-M); and Sesame (Sesamum indicum L.)-mustard (S-M)] in sub-plots. The mean mustard seed yield increased 28 and 11% under permanent beds with residue (PB+R) and zero tillage with residue (ZT+R) compared to conventional tillage without residue (CT-R), respectively. The mean seed yield of kharif crops also increased by 37.1 and 31.7% in the PB+R and ZT+R compared to CT-R, respectively. The maize-mustard (Mz-M) cropping system recorded significantly higher yield of mustard across the years followed by greengram-mustard (GG-M) cropping system. The mean mustard equivalent yield (MEY) increased by 33.4 and 24.2% in PB+R and ZT+R over the CT-R, respectively. The total system grain yield (TSGY) also increased by 29.6 and 14.7% in the PB+R and ZT+R over the CT-R, respectively. Among the cropping systems, GG-M followed by Mz-M system recorded highest MEY and TSGY in both the years. The Mz-M cropping system under PB+R recorded maximum net returns and B:C ratio which was higher by 40.7 and 41.1 compared to traditional F-M cropping system under CT-R, respectively. Thus, CA-based Mz-M/GG-M system should be out scaled in the traditional rainfed mustard based production system to improve the farm production and income on holistic basis to increase the edible oil production in the country.